Are Ghanaian women meeting the WHO recommended maternal healthcare (MCH) utilisation? Evidence from a national survey - Edward Kwabena Ameyaw; Kwamena Sekyi Dickson; Kenneth Setorwu Adde (BMC, 2021)
Abstract Background To achieve the Sustainable Development Goal target 3.1, the World Health Organisation recommends that all pregnant women receive antenatal care (ANC) from skilled providers, utilise the services of a skilled birth attendant at birth and receive their first postnatal care (PNC) within the first 24 h after birth. In this paper, we examined the maternal characteristics that determine utilisation of skilled ANC, skilled birth attendance (SBA), and PNC within the first 24 h after delivery in Ghana. Methods We used data from the 2014 Ghana Demographic and Health Survey. Women aged 15-49 with birth history not exceeding five before the survey were included in the study. A total of 2839 women were included. Binary logistic regression was employed at a 95% level of significance to determine the association between maternal factors and maternal healthcare (MCH) utilisation. Bivariate and multivariate regression was subsequently used to assess the drivers. Results High proportion of women had ANC (93.2%) with skilled providers compared to the proportion that had SBA (76.9%) and PNC within the first 24 h after delivery (25.8%). Only 21.2% utilised all three components of MCH. Women who were covered by national health insurance scheme (NHIS) had a higher likelihood (AOR = 1.31, CI = 1.04 - 1.64) of utilising all three components of MCH as compared to those who were not covered by NHIS. Women with poorer wealth status (AOR = 0.72, CI = 0.53 - 0.97) and those living with partners (AOR = 0.65, CI = 0.49 - 0.86) were less likely to utilise all three MCH components compared to women with poorest wealth status and the married respectively. Conclusion The realisation that poorer women, those unsubscribed to NHIS and women living with partners have a lower likelihood of utilising the WHO recommended MCH strongly suggest that it is crucial for the Ministry of Health and the Ghana Health Service to take pragmatic steps to increase education about the importance of having ANC with a skilled provider, SBA, and benefits of having the first 24 h recommended PNC.